2021
DOI: 10.3390/cancers13236090
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of PD-L1 Expression in Invasive Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Programmed death ligand 1 (PD-L1) has been investigated in various types of cancer; however, the role of PD-L1 expression in breast cancer remains controversial. We performed a systematic review and meta-analysis to assess the association of PD-L1 expression with clinicopathological variables, overall survival (OS), and disease-free survival (DFS) in invasive breast cancer. A total of 965 articles were included from CINAHL, Embase, PubMed, and Scopus databases. Of these, 22 studies encompassing 6468 cases of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
(165 reference statements)
0
16
0
5
Order By: Relevance
“…26,27 For instance, HER2-positive status provides prognostic information in node-negative breast cancer and predictive information in selecting targeted and systemic therapy. [28][29][30] One possible explanation from our study was the small number of patients with unfavorable results (n=26), which might limit our statistical power in detecting these associations. Further research with a larger sample size and the number of outcomes is needed.…”
Section: Discussionmentioning
confidence: 92%
“…26,27 For instance, HER2-positive status provides prognostic information in node-negative breast cancer and predictive information in selecting targeted and systemic therapy. [28][29][30] One possible explanation from our study was the small number of patients with unfavorable results (n=26), which might limit our statistical power in detecting these associations. Further research with a larger sample size and the number of outcomes is needed.…”
Section: Discussionmentioning
confidence: 92%
“…Studies demonstrated that PD-L1 expression varies across different BC subtypes with positivity rates ranging from 0-83% [19,20]. A higher rate of PD-L1 expression has been demonstrated in a subset of BCs with aggressive clinicopathological and immunohistochemical tumor features, such as grade 3 tumors, ER and PR negativity, or Ki-67 proliferation greater than 14%, and this was associated with lower overall survival (OS) [21,22]. A meta-analysis of 19,870 patients revealed a higher rate of PD-L1 expression in breast tumors with a pathological complete response (pCR) following neoadjuvant chemotherapy [21].…”
Section: Of 12mentioning
confidence: 99%
“…Its prognosis is very poor, mainly because of its high metastasis incidence and low efficacy of the current management protocols [ 2 , 3 ]. A worse overall survival (OS) in BC patients was associated with positive expression of PD-L1 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many tumors can upregulate the expression of PD-L1, inhibiting anti-tumor T-cell responses and avoiding immune surveillance and elimination. Furthermore, it has been found that the expression of PD-L1 is associated with shorter survival and poorer prognosis in many cancers, including BC [ 4 , 14 ]. TNBC is a highly aggressive metastatic cancer with a very high mortality rate [ 2 ], and 50% of these tumors showed a high level of PD-L1 expression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%